Enhanced extraction of bovine serum albumin with aqueous biphasic systems of phosphonium- and ammonium-based ionic liquids - Pereira, Matheus M.
Novel aqueous biphasic systems (ABS) composed of phosphonium- or ammonium-based ionic liquids (ILs), combined with a buffered aqueous solution of potassium citrate/citric acid (pH = 7.0), were investigated for the extraction of proteins. For that purpose, the phase diagrams, tie-lines and tie-line lengths were determined at 25 degrees C, and the performance of these ABS for the extraction of bovine serum albumin (BSA) was then evaluated. The obtained results reveal that, with the exception of the more hydrophobic ILs, most of the systems investigated allow the complete extraction of BSA for the IL-rich phase in a single-step. These remarkable extraction efficiencies are far superior to those afforded by more conventional extraction systems previously reported. The composition of the biphasic systems, i.e., the amount of phase-forming components, was also investigated aiming at reducing the overall costs of the process without losing efficiency on the protein extraction. It is shown that the extraction efficiencies of BSA are maintained at 100% up to high protein concentrations (at least up to 10 g L-1). The recovery of the BSA from the IL-rich phase by dialysis is also shown in addition to the demonstration of the IL recyclability and reusability, at least for 3 times. In the sequential three-step extractions (BSA recovery/IL reusability), the extraction efficiencies of BSA for the IL-rich phase were maintained at 100%. For the improved ABS, the preservation of the protein native conformation was confirmed by Size Exclusion High-Performance Liquid Chromatography (used also as the quantification method) and by Fourier Transform Infra-Red spectroscopy. According to the results herein reported, ABS composed of phosphonium- or ammonium-based ILs and a biodegradable organic salt represent an alternative and remarkable platform for the extraction of BSA and may be extended to other proteins of interest. (C) 2015 Elsevier B.V. All rights reserved.